ANALYTICAL INSTRUMENT FOR THE EFFICIENCY OF THE USE OF RESTRUCTURING ASSETS FOR PROVISION OF ACTIVITY AND SELF-DEVELOPED ENTERPRISE DEVELOPMENT - Tsarenko, O.V. (The actual problems of regional economy development, 2018)
The article discusses the essence of current assets, and the risks associated with the process of forming their optimal structure. The influence of acceleration of turnover of circulating assets on the financial results of the enterprise activity is determined. The procedures of constant monitoring and analysis of the efficiency of the use of circulating assets are argued, which provides the management of the enterprise with timely information and allows to make informed managerial decisions on the optimal formation of the volume of circulating assets. The definition of reversible (mobile) assets as a system-forming element of polyfunctional changes in the scale of development of structural units on the one hand - a commercial product (service) on the basis of its material and material form, on the other - as activity of its direct creation and realization in the continuous cycle of ownership forms, which ensures: the agglomeration of different entities by the nature of the subject-oriented relations and the consolidation of interaction between all hierarchical levels. It is shown that when enterprises are fully self-financing, determining the optimal demand for working assets as a whole and for each component is important. An increase in the amount of current assets above this optimum leads to a loss due to excessive funds and the non-use of available material resources. At the same time, the reduction in working capital of enterprises, compared with their optimal values, causes simple equipment and other losses associated with the lack of certain or other necessary material resources. Rational management of working assets involves their optimization based on the needs of the enterprise. The directions of increase of efficiency of use of circulating assets depending on the cycle of work are grounded, which include economic-financial determinants, sources and regulatory tools for creation of effective policy of management of circulating assets in the general strategy of asset management of the enterprise for formation of necessary volume and composition of working assets, optimization of sources of their financing . The criteria for increasing the efficiency of use of circulating assets are worked out, which include: acceleration of their turnover by increasing the volume of products sold with the provision of its long-term release to order, as well as a thorough and timely selection of products for shipment; the use of methods for the valuation of current assets - a method of direct calculation, analytical (experimental-statistical) method, coefficient method; increase of liquidity and solvency of the enterprise; observance of the optimal ratio of own and borrowed working assets, as well as budgeting of current revenues and expenditures. For system optimization of structural units, the following ways of managing receivables, such as providing discounts for quick payment, are defined; factoring; control of payments settlements with buyers in the case of deferred (past due) receivables; system analysis of the ratio of receivables and payables; classification of receivables depending on its quality and creation of bad debt reserves; monitoring of accounts receivable and comparing its indicators with the same indicators by industry, competitors and data of past years. Depending on the cycle of work, the priority ways to increase the efficiency of the use of working assets are determined: reduction of inventory in warehouses due to the reduction of excess inventory of materials, due to improved supply, by reducing the cost of materials per unit of output; reduction of the duration of the production cycle of the main products due to the use of new technology and technology, increase of productivity, norms of expenses of resources, decrease of time of stay in parts of parts, assembly units; reducing the balances of unrealized products through accelerating sales, increasing the efficiency of the marketing service, improving the calculations, improving the completeness of deliveries; increasing the rhythm of production due to the uniformity of release and shipment of products, improvement of planning and organization of production.